Deteksi Awal Ketahanan Beberapa Aksesi Pisang Lokal dan Hasil Persilangan terhadap Penyakit Layu Fusarium (Foc VCG 01213/16 TR4) - Handayani, Tri; Martanti, Diyah; S. Poerba, Yuyu, Witjaksono (Indonesian Society for Horticulture / Department of Agronomy and Horticulture, 2017)
ABSTRACTEarly detection for Fusarium wilt resistant of banana plants can be done at seedling phase under greenhouse condition. The purpose of early detection was to screen and evaluate some number of local and hybrid accession of banana plants for resistance to Fusarium oxysporum f. sp. cubense (Foc VCG 01213/16 TR4 or Foc TR4). The treatments were done by immersing the root seedling in Fusarium inoculant at concentration of 106 conidia mL-1, for 2 hours, then planted in sterile sand media and placed in container with